Molecular basis for protein–protein interactions - Seychell, Brandon Charles; Beck, Tobias (Beilstein Journal of Organic Chemistry, 2021)
This minireview provides an overview on the current knowledge of protein–protein interactions, common characterisation methods to characterise them, and their role in protein complex formation with some examples. A deep understanding of protein–protein interactions and their molecular interactions is important for a number of applications, including drug design. Protein–protein interactions and their discovery are thus an interesting avenue for understanding how protein complexes, which make up the majority of proteins, work.
Keywords: characterisation methods; heterooligomeric complex; homooligomeric complex; molecular interactions; protein–protein interactions